(3GdJPcQI aj GMcGe GdLhGgQ hGdGZQGVs - (3CHheMeO GdMSf Hf CMeO Hf eJhjgs
(3ChdgG (B:s
(3gPg JPcQI JTJed Ydi HjGf GMcGe GdeYdheGJ hGhUGagG hJLeY Edi GdGjLGR ai Gdbhd GSJbUGA ai GdGOdI s
(3BNQgG (B:s
(3aYdi GdWQjbI jMJhi GdcdGe ai HjhJ GdJVGO ef GdQWhHGJ Je GdLRA GdChd ef cJGH GdJPcQI s
(3fSNI NRGFfjI HQSe GdefUhQ HGddg YHO Gddg Hf MeRI Gdjefi GdRjOji (B614 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs